Using Artificial Intelligence to Enhance Judicial Efficiency from the Perspective of the Right to a Fair Trial* - Skutele, Signe (Teisė, 2025)
Artificial intelligence (AI) has rapidly transformed public and private spheres, offering new opportunities for efficiency and innovation while raising complex legal, ethical, and social challenges. Its integration into the judiciary presents a key legal and human rights issue, with significant implications for judicial efficiency and modernization. The research aims to explore the potential of AI in improving judicial efficiency, without compromising the right to a fair trial. It examines the impact of the justice system digitalization, by defining the scope of the judicial efficiency and identifying the fundamental principles that should be clarified and promoted in the process. The research encompasses national and international legal frameworks, reports, and policy documents, as well as academic literature on the use of AI in the judiciary. While the application of AI in the judiciary is often associated with functional optimization – such as automated judgment drafting – the research also highlights the importance of addressing broader dimensions of efficiency, including procedural, institutional, and individual aspects. Thus, in this research, the author emphasizes the introduction of AI in the justice system as a broader and strategically targeted set of actions, focusing on the use of different AI systems to improve various elements of judicial efficiency.